Adjusted 0-1 knapsack problem in cargo flow by using artificial bee colony algorithm / Siti Hafawati Jamaluddin ... [et al.] - Jamaluddin, Siti Hafawati; Md Jani, Nor Zuliiziati; Mahmud, Norwaziah; Muhammat Pazil, Nur Syuhada (Universiti Teknologi MARA, Perlis, 2022)
This study describes the problem with the knapsack that occurred in the cargo flow. The problem of the knapsack is the problem of optimisation used to illustrate the problem and the solution in which each set of items has its own specific value and weight. With its total value as much as possible, the number of items that may become less or at least equal to or equal to the limit. Therefore, the aim of this study is to determine the minimum total cost of 30 shipments based on volume by using Artificial Bee Colony (ABC) algorithm in order to achieving the highest profit. ABC algorithm was derived from the bee colony which consists of four phases of initialisation, employed bees, onlooker bees and scout bees. Based on the result obtained, the total cost of the shipment is 402.377 tons per km which starting from the Shipment 25 with 2 560 000 tons per year for 0.111 tons per km and ends with Shipment 21 with 2 250 000 tons per year for 0.129 tons per km.